High school students' attitudes towards spiders: A cross-cultural comparison - (:unkn) unknown (My University, 2010)
Spiders are traditionally considered to be among the least popular of animals. Current evidence suggests that a negative attitude towards spiders could be influenced by both cultural and evolutionary pressures. Some researchers suggest that science education activities could positively influence students' perceptions of spiders. Their evidence is, however, ambivalent. Using a five-point score Likert-type questionnaire in which the items were developed in a similar way to four of Keller's categories of attitude (scientistic, negativistic, naturalistic, and ecologistic) towards invertebrates, we compared the level of knowledge of and attitudes towards spiders of high school students from two countries, Slovakia (n = 354) and South Africa (n = 382). The students represented different cultures and followed dissimilar science education curricula. Only among the Slovakian students there was a statistically significant, but low correlation between knowledge and attitude (r = .30). The Slovakian students had less fear of spiders. The South African students scored higher in the categories of scientistic, naturalistic and ecologistic attitudes. Comparison of attitude towards spiders of indigenous Africans from coeducational Catholic schools revealed that, South African students have greater fear of spiders than Slovakian students, supporting the biological preparedness hypothesis. This hypothesis predicts a greater fear of spiders in South Africa than in Europe since several South African spiders possess venoms that are dangerous to humans. The results of this study are discussed from science education, cultural and evolutionary perspectives.
Keywords: African Research